2023
DOI: 10.1007/s00421-023-05275-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cytokine responses to acute strength exercise between oral contraceptive users and naturally cycling women

Abstract: Purpose Cytokines are released as part of an inflammatory reaction in response to strength exercise to initiate muscle repair and morphological adaptations. Whether hormonal fluctuations induced by the menstrual cycle or oral contraceptives affect inflammatory responses to strength exercise remains unknown. Therefore, we aimed to compare the response of cytokines after acute strength exercise in naturally menstruating women and oral contraceptive users. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Thirty‐four studies, including 64 intervention groups with a total of 495 participants (89% male/11% female), were included in this systematic review and meta‐analysis. From the total of 34 studies included in the meta‐analyses, 29 studies investigated IL‐6 with 56 effect sizes, 55,74‐100 11 examined IL‐10 with 24 effect sizes, 55,74,75,77‐80,85,88,89,97 and further 5 analyzed IL‐1ra with 14 effect sizes 77,83‐85,97 . Nine studies with 15 effect sizes looked into TNF‐α, 75,78,87,89,96,98,101‐103 and five studies accounting for eight effect sizes investigated IL‐15 33,88,91,104,105 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐four studies, including 64 intervention groups with a total of 495 participants (89% male/11% female), were included in this systematic review and meta‐analysis. From the total of 34 studies included in the meta‐analyses, 29 studies investigated IL‐6 with 56 effect sizes, 55,74‐100 11 examined IL‐10 with 24 effect sizes, 55,74,75,77‐80,85,88,89,97 and further 5 analyzed IL‐1ra with 14 effect sizes 77,83‐85,97 . Nine studies with 15 effect sizes looked into TNF‐α, 75,78,87,89,96,98,101‐103 and five studies accounting for eight effect sizes investigated IL‐15 33,88,91,104,105 .…”
Section: Resultsmentioning
confidence: 99%
“…From the total of 34 studies included in the meta-analyses, 29 studies investigated IL-6 with 56 effect sizes, 55,74-100 11 examined IL-10 with 24 effect sizes, 55,74,75,[77][78][79][80]85,88,89,97 and further 5 analyzed IL-1ra with 14 effect sizes. 77,[83][84][85]97 Nine studies with 15 effect sizes looked into TNFα, 75,78,87,89,96,98,[101][102][103] and five studies accounting for eight effect sizes investigated IL-15. 33,88,91,104,105 As displayed in Table 2, only two studies investigated the effects of resistance exercise on female participants, 88,97 and two studies had at least one female intervention group investing sex-dependent differences in results.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies reported decrease in the levels of inflammatory cytokines such as IL-6 in COC users compared to naturally cycling women [35]. While in other studies, COC did not alter the levels of IL-6 and other related cytokines during exercise [43,44]. The duration and intensity of exercise among other factors like age appears to play a major role in regulating immune function [45,46].…”
Section: Introductionmentioning
confidence: 90%
“…In fact, available evidence regarding the effect of COC on the markers of immune activation [37][38][39][40][41] especially in exercise condition are limited and inconsistent. For instance, COC was shown to increase the levels of interleukin (IL)-1ra, IL-8 and Creactive protein (CRP) during exercise [42,43]. In contrast, some studies reported decrease in the levels of inflammatory cytokines such as IL-6 in COC users compared to naturally cycling women [35].…”
Section: Introductionmentioning
confidence: 99%